Transalveolar sinus floor elevation using osteotomes without grafting in severely atrophic maxilla: a 5-year prospective study - Gu, Ying-Xin; Shi, Jun-Yu; Zhuang, Long-Fei; Qian, Shu-Jiao; Mo, Jia-Ji; Lai, Hong-Chang (Clinical oral implants research, 2016)
Objective The aim of this study was to assess the clinical success of dental implants placed in severely atrophic maxilla (residual bone height ≤4 mm) using transalveolar sinus floor elevation (TSFE) without grafting. Furthermore, the implant stability during the healing period was also evaluated. Materials and methods Twenty five generally healthy patients with 37 Straumann® Standard Plus SLA implants were included in the study. After a modified Summers TSFE without grafting was performed, the smooth collar was embedded 0.5–1 mm beneath the cortical bone level. Follow‐ups were conducted at 12, 36, and 60 months after crown placement. Implant survival rate, resonance frequency analysis (RFA), and clinical and radiographic parameters were evaluated. Results At 5‐year follow‐up, 35 implants fulfilled the survival criteria, representing a 5‐year cumulative survival rate of 94.6% at implant level and 92% at subject level. The mean value of implant stability quotient (ISQ) ranged from 67.8 to 72.8, and the lowest values were reached at 4 weeks. No significant difference was found with the passage of time in modified plaque index (P = 0.92), pocket probing depth (P = 0.34), and modified bleeding index (P = 0.4). The average residual bone height was 2.81 mm (SD: 0.74 mm) in this study. The average crestal bone loss (CBL) significantly increased from 0.83 mm at 1‐year examination to 1.47 mm at 3‐year examination (P < 0.001). The average CBL remained stable at years 3 and 5 (1.47 vs. 1.54 mm, P = 0.083). Conclusion According to the current evidence, it is feasible to place cylindrical implants in severely atrophic maxilla. High survival rate could be achieved following TSFE without grafting at least within 5‐year follow‐up.